Following half-season intensive grazing on native pasture with alfalfa or sudangrass grazing and/or feedlot finishing - Helsel, R.M.; Posler, Gerry L.; Riley, Jack G.; Smith, E.F.; Ward, G.M. (Kansas State University. Agricultural Experiment Station, 2011)
Late summer grazing of alfalfa or sudangrass by cattle coming off half-season, double-stocked native grazing showed no advantage over immediate feedlot finishing. Late-summer grazers gained less in the feedlot and required about the same feeding period as those animals taken to the feedlots in midsummer.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Alfalfa; Sudangrass; Feedlot finishing